On The Phenomenon Of Enttäuschung: A Rejoinder To Roy Schafer’s Psychoanalytic Formulation Of ‘Disappointment’ And ‘Disappointedness’ (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper re-examines psychoanalytic formulations of disappointment. Using the philosophical insights of Karl Jaspers, I propose that existential analysis could more usefully focus on the phenomenon of Enttäuschung (disillusionment), the client's confrontation with the reality of situations and the adoption of their attitude towards this.
Keywords: Enttäuschung; disappointment; disillusionment; Jaspers